Assessment of estrogenic activity and total lipids in maternal biological samples (serum and breast milk) - R. Sapbamrer (2018)
The present study investigated estrogenic activity and total lipid levels in maternal serum and breast milk. The study was performed with 50 mothers from Fang district of northern Thailand. Maternal serum was collected 5 times, including the second trimester, pre-delivery period, delivery period, and lactating period at day 30 and day 60. Breast milk was collected 7 times, including day 1, 7, 14, 21, 30, 45, and 60 of lactation. There were the same patterns of variation between estrogenicity and total lipid levels both in serum and breast milk. The correlation between serum estrogenicity and serum total lipids was found with a correlation coefficient (r) ranging from 0.403 to 0.661. However, no correlation was found between milk estrogenicity and milk total lipids. The results therefore suggest that lipid contents might be the major factors affecting the variation of estrogenicity levels, and xenoestrogens, which the mother subjects exposed, were lipophilic pollutants. The remarkable findings were that the mean levels of estrogenicity in breast milk were approximately 8-13.5 times higher than those in maternal serum compared at the same period. However, no correlation was found between estrogenicity levels in serum and breast milk, leading to decreased accuracy in predicted infant exposure by maternal serum. © 2009 Elsevier Inc.